Selection of Shared and Neoantigen-Reactive T Cells for Adoptive Cell Therapy Based on CD137 Separation - Seliktar-Ofir, Sivan; Merhavi-Shoham, Efrat; Itzhaki, Orit; Yunger, Sharon; Markel, Gal; Schachter, Jacob; Besser, Michal J. (Frontiers in Immunology, 2017)
Adoptive cell therapy (ACT) of autologous Tumor Infiltration T Lymphocytes (TIL) is an effective immunotherapy for patients with solid tumors, yielding objective response rates of around 40% in refractory patients with metastatic melanoma. Most clinical centers utilize bulk, randomly isolated TIL from the tumor tissue for ex vivo expansion and infusion. Only a minor fraction of the administered T cells recognizes tumor antigens, such as shared and mutation-derived neoantigens, and consequently eliminates the tumor. Thus, there are many ongoing effects to identify and select tumor specific TIL for therapy, however those approaches are very costly and require months, which is unreasonable for most metastatic patients. CD137 (4-1BB) has been identified as a co-stimulatory marker which is induced upon the specific interaction of T cells with their target cell. Therefore, CD137 can be a useful biomarker and an important tool for the selection of tumor reactive T cells. Here, we developed and validated a simple and time efficient method for the selection of CD137 expressing T cells for therapy based on magnetic beads separation. CD137 selection was performed with clinical grade compliant reagents and TIL were expanded in a large-scale manner to meet cell numbers required for the patient setting in a GMP facility. For the first time the methodology was designed to comply with both clinical needs and limitations, and its feasibility was assessed. CD137 selected TIL demonstrated significantly increased anti-tumor reactivity and were enriched for T cells recognizing neoantigens as well as shared tumor antigens. CD137 based selection enabled the enrichment of tumor reactive T cells without the necessity of knowing the epitope specificity or the antigen type. The direct implementation of the CD137 separation method to the cell production of TIL may provide a simple way to improve the clinical efficiency of TIL ACT.